Fasting-Mimicking-Diet does not reduce skeletal muscle function in healthy young adults: a randomized control trial - Nardon, Mauro; Venturelli, Massimo; Ruzzante, Federico; Longo, Valter D.; Bertucco, Matteo (European journal of applied physiology, 2022)
Purpose The aim of this study was to evaluate the short- and long-term effects of the Fasting-Mimicking-Diet (FMD) intervention on neuromuscular parameters of force production in healthy young men. Methods Twenty-four physically active men completed the study. Participants were randomly assigned to Fasting-Mimicking (FMD) or Normal Diet (ND) and asked to follow three cycles of dietary intervention. Neuromuscular parameters of force production during maximal voluntary isometric contractions (MVCs) with the leg extensors muscles and anthropometrics were measured at baseline (T0), at the end of the first cycle (T1), and 7–10 days after the 3rd cycle of the nutritional intervention (T2). The study was registered on Clinicaltrials.gov (No. NCT04476615). Results There was a significant decrease in body mass at T1 for FMD (− 2.6 kg, ∆ from baseline, on average; p < 0.05) but not in ND (− 0.1 kg;). Neuromuscular parameters of force production, muscle volume, and MVC torque did not change or differ between groups across visits. Results were similar even when parameters were normalized by muscle volume. Conclusion The consumption of FMD in a group of young healthy male subjects showed to be feasible, and it did not affect neuromuscular parameters of force production. The results suggest that FMD could be safely adopted by strength athletes without detrimental effects on force and muscle volume. Further research in clinical population at risk of muscle mass loss, such as elderly and obese subjects with sarcopenia, is warranted.